SPATIAL ORGANIZATION OF BUSINESS - FROM A CLASSIC APPROACH TO AN INNOVATIVE ONE - MATICIUC MĂDĂLINA DUMITRIȚA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
This paper aims to examine whether industrial parks, industrial districts, science and technology parks and business incubators could be considered as precursor forms of cluster development. In this regard, we conducted a descriptive analysis of the common and different aspects that arise in various forms of spatial organization of business. We decided to compare them two by two to observe, in a detailed form, how industrial parks, industrial districts, science and technology parks and business incubators resemble or differ from the innovative form of spatial business organization, the cluster. Thus, the paper focuses on contextualizing and conceptualizing the forms of spatial organization of business by researching the literature, identifying specific elements in an orderly and relevant sense. The research technique is that of reviewing the specialized literature. The documentary literature identified in the Web of Science database was used as documentary sources, especially on the scientific articles that attest to the different types of spatial organization of business. The work does not stop only at industrial parks, industrial districts, science and technology parks and business incubators and goes beyond a classic business approach, to one focused on innovation, such as clusters. Based on the characteristics identified in each of the materials studied, we presented the cluster so that it reflects what it represents at the moment, namely an innovative form of spatial business organization.